Nuclear Energy Safety and International Cooperation : Closing the World's Most Dangerous Reactors. - Meredith, III, Spencer Barrett (Routledge studies in environmental policy., 2014)
Twenty-five years after the Chernobyl explosion, disaster struck once more after a tsunami overwhelmed the considerable safety measures at the Fukushima nuclear power plant in Japan. However, Fukushima had put in place a solid containment structure to reduce the spread of radiation in the event of a worst-case scenario; Chernobyl did not. These two incidents highlight the importance of such safety measures, which were critically lacking in an entire class of Soviet-designed reactors. This book examines why five countries operating these dangerous reactors first signed internat.